Yield of maize in an intercropping system with peanut under nitrogen fertilization - S. P. Gomes; G. G. Sousa; R. S. Barbieri; F. H. R. Costa; H. C. Sousa; M. V. P. Souza; G. F. Goes; A. G. Silva; P. B. C. Cambissa; B. Baldé; J. M. P. Lima (Brazilian Journal of Biology)
Abstract Nitrogen fertilization can significantly enhance the productivity of maize and peanuts in an intercropping system. This study aimed to evaluate the impact of full, partial, or complementary substitution of nitrogen fertilization through intercropping with peanuts on leaf nutrient levels and maize yield. The experiment was conducted from February to May 2021, at an area belonging to the Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB) in Redenção, Ceará state (Brazil). The experimental design was a randomized block design with five treatments: MP0 (maize intercropped with peanuts without nitrogen fertilization), MP50 (maize intercropped with peanuts with 50% of the recommended nitrogen dose), MP100 (maize intercropped with peanuts with 100% of the recommended nitrogen dose), MN50 (maize in monoculture with 50% of the recommended nitrogen dose), and MN100 (maize in monoculture with 100% of the recommended nitrogen dose), each with four replications. The results indicate that intercropping maize with peanuts improves the efficiency of nitrogen fertilization and land use. However, complete substitution of nitrogen fertilization in the maize-peanut intercropping system is not recommended due to the observed lower growth and yield indices.